2013
DOI: 10.1371/journal.pone.0084149
|View full text |Cite
|
Sign up to set email alerts
|

An Allele of Sequoia Dominantly Enhances a Trio Mutant Phenotype to Influence Drosophila Larval Behavior

Abstract: The transition of Drosophila third instar larvae from feeding, photo-phobic foragers to non-feeding, photo-neutral wanderers is a classic behavioral switch that precedes pupariation. The neuronal network responsible for this behavior has recently begun to be defined. Previous genetic analyses have identified signaling components for food and light sensory inputs and neuropeptide hormonal outputs as being critical for the forager to wanderer transition. Trio is a Rho-Guanine Nucleotide Exchange Factor integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We had previously shown that the seq 9 . 17 allele acted as a dominant enhancer of a sensitized trio mutant background, blocking the larval-pupal transition [ 15 ]. This observation has allowed us to identify the tissue responsible for this phenotype by rescuing pupation via driving trio in various tissue-specific patterns with the GAL4-UAS system [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We had previously shown that the seq 9 . 17 allele acted as a dominant enhancer of a sensitized trio mutant background, blocking the larval-pupal transition [ 15 ]. This observation has allowed us to identify the tissue responsible for this phenotype by rescuing pupation via driving trio in various tissue-specific patterns with the GAL4-UAS system [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, our simple trio mutant genotype ( trio M89 / trio P1 ) did not show a reduction in dendrite density nor an alteration in dendritic branch frequency ( Fig 3A and 3B ) presumably because we utilized the trio hypomorphic allele trio P1 . This hypomorphic allele was originally used to provide a sensitized genetic background in our screen for dominant second-site modifiers of the trio mutant phenotype [ 15 ]. The increased dendritic branch frequency observed in the larvae that generally failed to undergo the larval-pupal transition ( seq 9 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations